Analisis Kinerja Jaringan Wireless LAN dengan Menggunakan Metode QoS dan RMA pada SD Negeri 014 Sangasanga - Maulidin, Achmad; Pranoto, Wawan Joko; Hallim, Abdul (YASIN, 2025)
The quality of the wireless LAN network at SD Negeri 014 Sangasanga is suboptimal, particularly during the implementation of the Computer-Based National Assessment (ANBK). This condition leads to network overload and decreased performance, which disrupts the smooth execution of ANBK. This study aims to analyze network performance using Quality of Service (QoS) and Reliability, Maintainability, Availability (RMA) methods, focusing on throughput, packet loss, delay, and jitter parameters. Measurements were conducted using Wireshark and PRTG tools during ANBK sessions. The research method involves collecting network performance data under actual conditions. The results show that the throughput parameter is in the poor category, averaging 1,200 Kbps, with a peak value of 3,056 Kbps and a low of 10 Kbps. Packet loss demonstrated excellent performance with 0% recorded across all sessions. The average delay reached 46 ms, ranging from 2.7 ms to 430 ms, mostly meeting TIPHON standards. Jitter averaged 28.4 ms, with stable results despite occasional spikes in certain sessions. The findings highlight the need for better network management to support stable ANBK implementation. Recommendations include improving network infrastructure with more reliable devices and applying efficient bandwidth management techniques to ensure stable network performance during ANBK sessions.